EVALUASI TINGKAT EFISIENSI BANK PEMBIAYAAN RAKYAT SYARIAH DI PROVINSI ACEH DENGAN METODE DATA ENVELOPMENT ANALYSIS - Kismawadi, Early Ridho; Junaidi (JURNAL EKONOMI DAN BISNIS ISLAM, 2018)
In this paper will discuss the efficiency of Islamic banking, especially Islamic Rural Banks (Sharia BPR) in Aceh Province, the approach used in calculating efficiency is the Data Envelopment Analysis (DEA) method, with the help of DEAP 2.1 software, obtained that Sharia BPR in Aceh Province the majority have operated efficiently.